Complaint in Tax Administration as an Instrument to Ensure Good Administration - Marethová, Zuzana (Public Governance, Administration and Finances Law Review, 2018)
This contribution deals with the legal institute of complaint as an instrument to ensure good administration, more precisely good tax administration. The main aim of the contribution is to confirm or disprove the hypothesis that a complaint is an institute that effectively protects people involved in tax administration and thereby mediates good governance. In the contribution, the method of analysis will be used to analyse and define theory and legal regulation.